Intravenous γ Globulin for Intractable Abdominal Pain due to IgA Vasculitis - George Naifa; George Totikidis; Sonia Alexiadou; Christina Kolona; Elpis Mantadakis (Hindawi Limited, 2020)
IgA vasculitis (formerly known as Henoch-Schönlein purpura or anaphylactoid purpura) is a usually benign vasculitis that affects children of school age. The disease is characterized by the tetrad of palpable purpura, arthralgia/arthritis, abdominal pain, and hematuria. Treatment of IgA vasculitis is mainly supportive, with administration of simple analgesics. Corticosteroids have been shown to reduce and/or ameliorate the occurrence of abdominal pain which may be severe. We present two children with IgA vasculitis and severe abdominal pain despite corticosteroid administration, who responded promptly to intravenous γ globulin (IVIg) with complete resolution of their symptoms and review of the relevant medical literature. Given the toxicity and/or need for long-term administration of other second-line immunosuppressive therapies in corticosteroid-resistant IgA vasculitis, such as rituximab, cyclosporine, cyclophosphamide, azathioprine, or colchicine, we propose that IVIg may be a useful and safe treatment option, although randomized controlled clinical trials are needed in order to clarify its role in the treatment of abdominal pain in IgA vasculitis.